Analisis Laporan Keuangan (Studi Kasus Pada PT. Akbar Indo Makmur Tbk) - Tala, Kezia Rachel Andrea; Faraswati, Dwi; Sari, Dina Puspita; Korompis, Yudistira Daniel (Jurnal Ilmiah Wahana Pendidikan, 2025)
The purpose of conducting this research and making a journal is to find out how financial performance is based on financial ratios at PT. AKBAR INDO MAKMUR Tbk in 2022-2023. The ratio used based on the analysis in this research is the Solvency Ratio. The solvency ratio was chosen because of its ability to measure a company's ability to meet short-term and long-term obligations. This research is also descriptive in nature, aiming to provide an overview of a phenomenon based on data collected systematically and accurately. Apart from that, the data taken in this research is the Financial Report of PT. AKBAR INDO MAKMUR Tbk in 2022-2023. For the results of the analysis based on the calculation of the Debt to Asset Ratio at Pt. Akbar Indo Makmur in 2022 will be 46.84%, while for 2023 it will be 53.16%. And for the results of the analysis, based on the calculation of the Debt to Equity Ratio at Pt. Akbar Indo Makmur in 2022 will be 88.12% while in 2023 it will be 113.51%. Debt to Asset Ratio is a ratio that measures the percentage of funds that come from debt. Then the Debt to Equity Ratio is a ratio used to determine the relationship between long-term debt and the amount of own capital that has been provided by the company owner. Keywords : Financial Report Analysis, Solvency, Debt to Total Ratio, Debt to Equity Ratio.